Pengaruh Kecepatan Putar Spindel dalam Pengujian Viskositas Produk UQ. Black QHS dengan Metode ANOVA (Studi Kasus PT. Mata Pelangi Chemindo) - Dino Caesaron; Sri Septyan Ayu Nintyas (Universitas Bunda Mulia, 2017)
In the chemical industry, especially the manufacture of the assorted colors pasta water base (Uniqua/UQ), visual pasta is very important because it can facilitate the mixing and prevent separation between the solvent and solute. To determine the level of viscosity or viscosity pastes used the color measuring instrument called viscometer. The viscometer is often used called Brookfield viscometer, which in this viscometer there is some speed rotary spindle. To standardize the spindle rotational speed to be used in testing UQ. Black QHS paste viscosity then conducted experimental research. In these experiments using ANOVA with one factor or one-way factor. This factor is the rotational speed of level 60, 30.12, 6 and 3 rpm. The result of these experiments is the spindle rotational speed affects the color paste viscosity test result.The results of these studies are the spindle rotational speed affects the color paste viscosity test results. Future studies may focus on testing the spindle rotational speed level best to get a good viscosity.Keywords: Viscosity, Viscometer, Experimental Research, ANOVA